Resolving the individual disputes in the era of Prophet (PBUH): In the light of Prophetic Seerah - Usman Abbas; Dr Attiq Ur Rehman (jihat-ul-islam, 2022)
Conflicts occur because human beings differ in temperament, beliefs, civilizations and nations. Even in the time of the Holy Prophetﷺ, there were differences among the followers of Prophet .has used various methods to resolve these differences and disputes ﷺThe Holy Prophet .)احصہب ( He used to resolve disputes by implementing Hudoodullah properly. Sometimes he would end the conflict by eliminating the habits of ignorance. Ever issued new rules for resolving disputes. Sometimes they would order to do well to each other in order to resolve the dispute. Mentioning the kindness of a good friend will resolve the dispute. Sometimes he used to say hard to resolve disputes. Sometimes he would issue a tolerance order to end the dispute. He used to involve the society in resolving disputes. The aim was to make the society peaceful and ideal.